The long-term outcome of children with refractory epilepsy after a vagal nerve stimulator implantation: CHU Sainte-Justine experience. (3rd June 2015) - Kaseka, ML; Carmant, LS; Desplats, E; Crevier, L; Major, P; Diadori, P; Lortie, A; Mercier, C; Carmant, L
Abstract : Background: Debate persists in Canada about the cost and benefit of vagal nerve stimulation in patients with refractory epilepsy. The aim of our study was to evaluate the impact of a vagal nerve stimulator on the seizure frequency and the admission rate of children with refractory epilepsies over five years of follow-up. Methods: 52 patients were implanted between 2000-2013. Of these, 37 were followed at CHU Sainte-Justine and 21 kept seizure diaries. Seizure frequency was compared to the baseline at 6 months, 12 months, 24 months and 60 months of follow up using a multivariate ANOVA analysis. The hospitalization rate was calculated as the mean difference between the number of hospitalizations prior to and after the implantation. Results: Seizure frequency decreased by 58% at 6 months, by 61% at 12 months, by 53% at 24 months and by 63% at 60 months of follow up respectively compared to the baseline (p<0.001). The hospitalization rate decreased by 50.87% after surgery (p<0.001). Conclusion: In our population, vagal nerve stimulation has a sustained impact on seizure frequency and hospitalization rates. This supports previous data from our group and others on cost-effectiveness of the technique in children with refractory epilepsy.